The effect of SI-G training on increase SQ among Iranian student in Malaysia. - Hosseini, Maryam; Elias, Habibah; Krauss, Steven Eric; Hassan, Siti Aishah (Canadian Center of Science and Education, 2010)
The main goal of this study is to determine whether SI-G training is able to help increase SQ. The present experimental study examined the effect of SI-G training on spiritual intelligence among Iranian students in Imam Khomeini School situated in Kuala Lumpur. This study has evaluated the effect of SI-G training program regarding the increasing SQ and its subscales. It evaluates the follow up test and the sustainability of the training program. The study shows that with SI-G training, spiritual intelligence and its subscales can be enhanced. Essentially, spiritual intelligence is a factor that affects training, practice and society in general, there is a relationship between most of the subscales of spiritual intelligence, therefore, training some of the subscales of spiritual intelligence can directly affect the other subscales. In this study, spiritual intelligence was measured by Integrated Spiritual Intelligence Scale (ISIS) employed to assess students' spiritual intelligence before and after the three weeks training period. Subsequent findings were discovered following SI-G training program. The result of the pre-test showed that most of the students have low SQ and the researcher has chosen 34 of them as sample. The sample gratitude has the lowest score and run through the highest mean between other subscales. This study revealed the significant relationship between 22 subscales of spiritual intelligence and between these subscales in relation to spiritual intelligence. The fmdings provided that SI-G training has effect on increasing spiritual intelligence and also improved most of the subscales. After 3 weeks, the researcher conducted a follow up test, comparing its result with post test, revealed that training program did not have good sustainability on SQ and some of the subscales. However, after comparing the results with pre-test, training program showed an effect on increasing SQ within three weeks of training.